Fabrication and surface enhanced Raman spectroscopy of single Au@SiO2 dimers linked by benzenedithiol. (8th December 2015) - Guo, Qinghua; Xu, Minmin; Yuan, Yaxian; Gu, Renao; Yao, Jianlin
Abstract : Metal nanoparticle dimers with controllable gap distance have attracted considerable attention because of their promising application in plasmonics. Generally, gaps with nanometer or subnanometer dimensions generate localized surface plasmon resonance (LSPR) coupling effect, thus contributing to a strong electromagnetic field for improving surface enhanced Raman scattering (SERS) effect. Here, we developed a facile approach to fabricate Au@SiO2 dimers through the steric hindrance effect, in which the SiO2 shell functioned as a block and a rigid dithiol molecule was employed as linker. The thickness of the SiO2 shell played a critical role in improving the yield of dimers. The dimerization efficiency increased significantly as the shell thickness decreased to ~1 nm. When 1, 4‐benzenedithiol was used as linker molecule, the yield of dimers was ~30%. Few dimers were obtained when mecaptobenzonic acid was used as linker. A thicker shell is associated with a low yield of dimer, whereas a thinner shell resulted in the formation of multimers and linear structures. The low number of linker molecules on the exposed area of monodisperse single nanoparticles and the lack of LSPR coupling effect ('hot spots') resulted in the disappearance of SERS signals of the linkers. The estimated SERS enhancement factor was about eight fold because of the strong coupling effect in the gap of the dimer with the distance of the dithiol molecular length. From the above results, SERS combined with SEM could be developed into powerful tools for monitoring the formation of dimers and positioning of single dimers. It may aid the control of assembly of Au nanoparticles and in probing key issues about SERS enhancements. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A facile approach was developed to fabricate Au@SiO2 dimers based on the steric hindrance effect, in which the SiO2 shell was severed as the block and a rigid dithiol molecule was used as the linker. The SERS enhancement factor of the dimer with the distance of the dithiol molecular length was about eight orders magnitude.